2018
DOI: 10.1101/cshperspect.a033688
|View full text |Cite|
|
Sign up to set email alerts
|

Metastases in Prostate Cancer

Abstract: Prostate cancer (PCa) prognosis and clinical outcome is directly dependent on metastatic occurrence. The bone microenvironment is a favorable metastatic niche. Different biological processes have been suggested to contribute to the osteotropism of PCa such as hemodynamics, bone-specific signaling interactions, and the "seed and soil" hypothesis. However, prevalence of disseminating tumor cells in the bone is not proportional to the actual occurrence of metastases, as not all patients will develop bone metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 130 publications
(131 reference statements)
4
25
0
Order By: Relevance
“…In addition, they develop a tropism for specific organ sites with the optimum conditions for their survival and growth. As Paget's paradigm suggests, both the tumor and its suitable microenvironment, the 'seed' and the 'soil', need to develop features to initiate a paracrine communication promoting the metastatic outgrowth [148].…”
Section: Stroma In Pca Bone Metastasismentioning
confidence: 99%
“…In addition, they develop a tropism for specific organ sites with the optimum conditions for their survival and growth. As Paget's paradigm suggests, both the tumor and its suitable microenvironment, the 'seed' and the 'soil', need to develop features to initiate a paracrine communication promoting the metastatic outgrowth [148].…”
Section: Stroma In Pca Bone Metastasismentioning
confidence: 99%
“…Tumorigenesis is highly associated with the interactions of cancer cells with their tumor microenvironment (TME). The interaction between the extracellular matrix (ECM) and stromal cells may further determine if the primary tumor is eradicated, metastasizes, or leads to dormant micrometastases [120,121]. Important components of the TME are the ECM, fibroblasts and myofibroblasts, mesenchymal stem cells, neuroendocrine cells (NE), adipose cells, immune and inflammatory cells, and the blood and lymphatic vascular networks.…”
Section: Promising Studiesmentioning
confidence: 99%
“…This exchange affects various tumor cell activities such as growth, invasion, metastasis, and response to therapeutic drugs. Some studies have shown that dissemination of tumor cells to the bone is not proportional to the actual incidence of metastases, indicating that the bone microenvironment greatly favors the localization and growth of metastatic prostate cancer cells [5], particularly, HRPC cells. Metastatic bone cancer tumors generally present as osteolytic lesions, whereas bone metastases of prostate cancer are primarily osteogenic lesions, suggesting that prostate cancer cells may affect the growth of osteoblasts and bone remodeling [6][7][8].…”
Section: Introductionmentioning
confidence: 99%